Analysis Of The Influence Of Islamic Income Ratio (Isir) And Equitable Distribution Ratio (Edr) On The Profitability Of Sharia Banks In Indonesia - nurahmadi Bi Rahmani (Journal Research of Economic and Bussiness, 2022)
This study aims to analyze the effect of Islamic Income Ratio (IsIR) and Equitable Distribution Ratio (EDR) on the profitability of Islamic banks in Indonesia for the period 2013-2020. This study uses a quantitative approach with secondary data. The analysis technique used is multiple linear regression where Islamic Income Ratio (IsIR) and Equitable Distribution Ratio (EDR) as independent variables and profitability proxied by Return On Assets (ROA) as the dependent variable with data processing analysis tools using SPSS 22.0. The results showed that partially Islamic Income Ratio (IsIR) had a positive and significant effect on profitability with a significance value of 0.000 less than 0.05. The results of subsequent research Equitable Distribution Ratio (EDR) has a positive and significant effect on profitability with a significance value of 0.000 less than 0.05. Simultaneously, Islamic Income Ratio (IsIR) and Equitable Distribution Ratio (EDR) have an effect on profitability with a significance value of 0.000, less than 0.05.